Electrophoretic pattern of seed proteins in Trifolium L. and its taxonomic implications - George, N. M.; Ghareeb, A.; Fawzi, N. M.; Saad, S. (Bangladesh Journal of Plant Taxonomy, 2013)
The taxonomic delimitations of 61 taxa of the genus Trifolium L. belonging to presently accepted five sections, namely Lotoidea, Mistyllus, Vesicaria, Chronosemium and Trifolium are evaluated, based on numerical analysis of their electrophoretic seed protein profiles. The dendrogram, resulted from the hierarchical cluster analysis of SDS-PAGE profiles of seed proteins conform, with some restrictions, to the present splitting of the genus Trifolium into the sections but not into the subsections and series. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15461 Bangladesh J. Plant Taxon. 20(1): 19-26, 2013 (June)